Children Learning About Secondhand Smoke (CLASS II): A Pilot Cluster Randomized Controlled Trial. Issue 5 (16th May 2018) - Siddiqi, Kamran; Huque, Rumana; Kanaan, Mona; Ahmed, Farid; Ferdous, Tarana; Shah, Sarwat; Jackson, Cath; Parrott, Steve; Ahluwalia, Jasjit S; Sheikh, Aziz
Abstract: Introduction: Children exposed to secondhand smoke (SHS) are at increased risk of respiratory illnesses. We piloted a Smoke Free Intervention (SFI) and trial methods before investigating its effectiveness and cost-effectiveness in primary school children. Methods: In a pilot cluster randomized controlled trial in Bangladesh, primary schools were allocated to usual education (control) or SFI, using minimization. Year-5 children were recruited. Masking treatment allocation was not possible. Delivered by schoolteachers, SFI consisted of two 45-min and four 15-min educational sessions. Our primary outcome was SHS exposure at two months post randomization, verified by children's salivary cotinine. The trial is registered at ISRCTN.com; ISRCTN68690577. Results: Between April 1, 2015 and June 30, 2015, we recruited 12 schools. Of the 484 children present in Year-5, 481 consented. Six schools were allocated to both SFI ( n = 245) and to usual education only ( n = 236). Of them, 450 children (SFI = 229; control = 221) who had cotinine levels indicative of SHS exposure were followed-up. All schools were retained, 91% children (208/229) in SFI and 88% (194/221) in the control arm completed primary outcome assessment. Their mean cotinine at the cluster level was 0.53 ng/ml ( SD 0.36) in SFI and 1.84 ng/ml ( SD 1.49) in the control arm—a mean difference of −1.31 ng/ml (95% CI = −2.86 to 0.24). Conclusion: It was feasible to recruit, randomize, and retain primary schools and children in our trial. Our study, though not powered to detect differences in mean cotinine between the two arms, provides estimates to inform the likely effect size for future trials. Implications: In countries with high smoking prevalence, children remain at risk of many conditions due to secondhand smoke exposure. There is little empirical evidence on the effectiveness and cost-effectiveness of interventions that can reduce their exposure to secondhand smoke at homes. CLASS II trial found that a school-based intervention (SFI) has the potential to reduce children's exposure to SHS—an approach that has been rarely used, but has considerable merit in school-based contexts. CLASS II trial provides key information to conduct a future definitive trial in this area of public health, which despite its importance has so far received little attention.